Assessing academic programs in higher education - Allen, Mary J. (Anker Pub., 2004)
Higher education professionals have moved from teaching- to learning-centered models for designing and assessing courses and curricula. Faculty work collaboratively to identify learning objectives and assessment strategies, set standards, design effective curricula and courses, assess the impact of their efforts on student learning, reflect on results, and implement appropriate changes to increase student learning. Assessment is an integral component of this learner-centered approach, and it involves the use of empirical data to refine programs and improve student learning. Based on the author's extensive experience conducting assessment training workshops, this book is an expansion of a workshop/consultation guide that has been used to provide assessment training to thousands of busy professionals. Assessing Academic Programs in Higher Education provides a comprehensive introduction to planning and implementing the assessment of college and university academic programs. Written for college and university administrators, assessment officers, department chairs, and faculty who are involved in developing and implementing assessment programs, this book is a realistic, pragmatic guide for developing and implementing meaningful, manageable, and sustainable assessment programs that focus faculty attention on student learning.